Amplitude-Energy Parameters of Acoustic Radiation with Composite Properties Changing and Mieses Destruction - Filonenko, Sergii; Stakhova, Anzhelika (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
The paper considers the modeling results influence of parameter that characterize composite properties on acoustic emission energy parameters during the composite material destruction by shear forces according to von Mises criterion. It is shown that the analyzed parameter increases a non-linear decrease of acoustic radiation maximum and total energy is occurs. It is determined that obtained patterns decrease of acoustic emission signals maximum and total energy are well described by power functions. It is shown that the most sensitive parameter of acoustic radiation to change the parameter characterizing composite properties is the acoustic emission signals total energy. It is determined that a decrease of acoustic emission signals maximum energy is ahead to decrease the maximum amplitude, and a decrease of acoustic emission signals total energy is ahead to decrease the maximum energy.